2017
DOI: 10.1016/j.chempr.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bright Long-Lived Luminescence of Silicon Nanocrystals Sensitized by Two-Photon Absorbing Antenna

Abstract: Summary Silicon nanocrystals of the average diameter of 5 nm, functionalized with 4,7-di(2-thienyl)-2,1,3-benzothiadiazole chromophores (TBT) and dodecyl chains, exhibit near-infrared emission upon one-photon (1P) excitation at 515 nm and two-photon (2P) excitation at 960 nm. By using TBT chromophores as an antenna we were able to enhance both 1P and 2P absorption cross-sections of the silicon nanocrystals to more efficiently excite their long-lived luminescence. These results chart a path to two-photon-excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The potential of 3D‐resolved two‐photon‐actuated nanomedicine has been exploited via various nanomaterials such as semiconductor and carbon nanodots, polymeric, organic, silicon, gold, graphene and graphene oxide, silica hybrid, and other inorganic nanomaterials. What are the advantages of silica‐based nanoparticles?…”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%
“…The potential of 3D‐resolved two‐photon‐actuated nanomedicine has been exploited via various nanomaterials such as semiconductor and carbon nanodots, polymeric, organic, silicon, gold, graphene and graphene oxide, silica hybrid, and other inorganic nanomaterials. What are the advantages of silica‐based nanoparticles?…”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%
“…Locritani et al demonstrated that bonded pyrene molecules can increase brightness of SiNc emission by almost 300% at 378 nm excitation. [29][30][31][32][33] In addition, Fermi et al indicated that a porphyrin chromophore can be also used as antenna for SiNc. However, a significant decrease in PLQY from 40% (for bare SiNc) to 8% (for the conjugates with the porphyrin) was observed upon excitation at 427 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant decrease in PLQY from 40% (for bare SiNc) to 8% (for the conjugates with the porphyrin) was observed upon excitation at 427 nm. 33 Recently, SiNc with attached diphenyl anthracene were used to improve optical properties of luminescent solar concentrators utilizing SiNc PL. 34 In our previous work, we have demonstrated that microwave-assisted hydrosilylation (MAH) method can produce SiNc exhibiting a PLQY of up to 40% and excellent long-term stability (6 months without decrease of PLQY).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PL from ncSi in the size range of interest is sufficiently red‐shifted from the absorption bands that it also falls within the bio‐transparency window. Fluorescent ncSi, including those composed of porous silicon and dye‐sensitized ncSi, have been shown to be useful for 2PA bio‐imaging …”
Section: Introductionmentioning
confidence: 99%